Moons - Welsbacher, Anne, frey50 (Minneapolis, Minn : Abdo & Daughters, 1997)
Describes our moon, its size and physical features, as well as the moons circling other planets in our solar system.
Includes index.
Keywords: Satellites; Moon -- Juvenile literature; Moon